2018
DOI: 10.1136/bjophthalmol-2018-312691
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness and harms of intravitreal antivascular endothelial growth factor agents for three retinal conditions: a systematic review and meta-analysis

Abstract: Intravitreal antivascular endothelial growth factor (VEGF) agents are widely used to treat ocular conditions but the benefits and harms of these treatments are uncertain. We conducted a systematic review to compare the effects of aflibercept, bevacizumab and ranibizumab on best-corrected visual acuity (BCVA) changes, quality of life and ocular or systemic adverse events in patients with neovascular age-related macular degeneration (NVAMD), diabetic macular oedema (DME) and central or branch retinal vein occlus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 58 publications
(8 reference statements)
0
38
0
14
Order By: Relevance
“…This may have been supported by the fact that anti-VEGF therapy remains a mainstay of treatment. 3,14,15 Similarly, advances in the medical field that has led to the increased population of the elderly who may have accounted for the cases of wet ARMD. 16 On the other hand, the proportion of patients with proliferative sickle cell retinopathy (SCR) needing intravitreal anti-VEGF has significantly reduced in the centre (from 16 to 3% over 5 years).…”
Section: Discussionmentioning
confidence: 99%
“…This may have been supported by the fact that anti-VEGF therapy remains a mainstay of treatment. 3,14,15 Similarly, advances in the medical field that has led to the increased population of the elderly who may have accounted for the cases of wet ARMD. 16 On the other hand, the proportion of patients with proliferative sickle cell retinopathy (SCR) needing intravitreal anti-VEGF has significantly reduced in the centre (from 16 to 3% over 5 years).…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the determinants might be complex, and they may also interact with each other. Still, multiple studies have proven bevacizumab to have comparable efficacy and safety to the registered anti-VEGF drugs, and there is also evidence that bevacizumab is the most costeffective drug for wet AMD [49,50]. In the end, the considerable European differences in ophthalmic bevacizumab use could mainly be a matter of principle and reflect differing attitudes towards off-label treatment itself.…”
Section: Discussionmentioning
confidence: 99%
“…In most clinical trials using intravitreal anti-VEGF therapy, the incidence of CVA, myocardial infarction (MI), and death is not significantly elevated, but these studies are underpowered for assessing small differences in rare events (23). Similarly, the incidence of systemic AEs did not differ between various anti-VEGF drugs, although one diabetic macular edema (DME) trial reported more arterial thrombotic events with ranibizumab versus aflibercept (24). Nevertheless, for some risk populations, such as patients with diabetes or a history of recent MI or CVA, there may be an increased risk with sustained suppression of systemic VEGF levels.…”
Section: Acknowledgmentsmentioning
confidence: 99%